Competencias digitales en docentes de educación primaria institución educativa 60026 que aplican la enseñanza virtual en tiempo de pandemia por COVID 19, Iquitos 2021 - Murrieta Izquierdo, Laydith (2023)
The general objective of the study was to explain digital skills in primary school teachers, educational institution No. 60026, who apply virtual teaching in times of the COVID.19 pandemic; the methodology included non-experimental research with a simple descriptive design, the sample that participated in the study was 36 primary level teachers, the survey was used as a technique and the Likert scale as an instrument. As a result of the study in the teachers of primary education of the Educational Institution 60026; 48.6% of the teachers occupy the average level, 45.7% the high level, 2.9% in the very high level and 2.9% in the Regular level; The main conclusion reached in the research is that teachers in general are at the average level in all the dimensions studied. From these data it can be indicated that teachers have to improve the level of knowledge and use of technologies to elevate the teaching-learning process.